Impact of ASPECTS on computed tomography angiography source images on outcome after thrombolysis or endovascular therapy in large vessel occlusions. (14th July 2016) - Wasser, K.; Papanagiotou, P.; Brunner, F.; Hildebrandt, H.; Winterhalter, M.; Roth, C.; Kastrup, A.
Abstract : Background and purpose: Endovascular therapy (ET) is superior to intravenous thrombolysis (IVT) in selected patients with anterior circulation large vessel occlusions. However, it is unclear if this positive effect also applies to patients with extensive early ischaemic changes. The aim of this study was to analyze the impact of the Alberta Stroke Program Early Computed Tomography Score (ASPECTS) on the CT angiography source images (SI) on outcome after ET or IVT. Methods: Using our prospectively obtained stroke database and the admission SI‐ASPECTS divided into three groups (0–5, 6–7 and 8–10), primarily the rates of good outcome [modified Rankin Scale (mRS) ≤2 at discharge] after either ET ( n = 255) or IVT ( n = 479) were compared. Results: A favorable SI‐ASPECTS (8–10) was present in 501 patients, 132 patients had a moderately favorable SI‐ASPECTS (6–7) and 101 patients had an unfavorable SI‐ASPECTS (0–5). Irrespective of the treatment modality, no patient with an unfavorable SI‐ASPECTS had a good outcome and 38% died during hospital stay. Whilst significantly more patients with a favorable SI‐ASPECTS had a good outcome after ET than after IVT (51% vs. 35%, P < 0.01), there was only a non‐significant trend towards a good outcome after ET than after IVT in patients with a moderately favorable ASPECTS (25% vs. 14%, P = 0.1). Conclusion: Patients with extensive early ischaemic changes on CT scans (SI‐ ASPECTS ≤5) might not profit from ET. The impact of ET on outcome in patients with moderately favorable SI‐ASPECTS should be addressed in further trials. Abstract : Clickhere for the corresponding questions to this CME article.